Prognostic significance of the allelic loss of the BRCA1 gene in colorectal cancer. Issue 12 (21st November 2003) - Garcia, J M; Rodriguez, R; Dominguez, G; Silva, J M; Provencio, M; Silva, J; Colmenarejo, A; Millan, I; Muñoz, C; Salas, C; Coca, S; España, P; et al.
Abstract : Background: Survival at the intermediate stage of colorectal cancer (CRC) is less predictable than in the early and advanced stages. Several genetic markers possibly involved in growth and progression of CRC can be used for prognosis. Aims: This study investigated the proportion of allelic loss (loss of heterozygosity (LOH)) at the BRCA1 locus in sporadic CRC and its value in patient prognosis. Patients and methods: A total of 314 patients were investigated for LOH at the BRCA1 locus using polymerase chain reaction by means of three intragenic polymorphic microsatellite markers. Allelic losses were compared with clinicopathological characteristics of patients, recurrence rate, disease free survival (DFS), and overall survival. Results: Twenty six patients were excluded because of microsatellite instability. Of the remaining 288 cases, 244 (84.7%) were informative, with 97 (39.8%) patients bearing BRCA1 LOH. Recurrence rate was higher in patients with LOH (p = 0.0003), and DFS was 73.3% (SEM 5.7) at five years in patients without LOH, and 49.2% (7.1) in cases with positive allelic loss (p = 0.0004). Retention of alleles at the BRCA1 locus was associated with a favourable DFS in stages I and II (p<0.05). The presence of LOH was also significantly associated with short overall survival (p = 0.02). Multivariate analysis in the complete series showed that stage (p = 0.006) and lymph node metastases (⩾4 nodes, p = 0.0001; 1–3 nodes, p = 0.038) were independent prognostic factors. However, multivariate study by stages revealed that BRCA1 LOH was an independent prognostic factor in stages I and II (p = 0.001). Conclusions: BRCA1 LOH is a molecular alteration present in CRC, with unfavourable repercussions for overall survival, that could be considered as an outstanding independent prognostic factor in stages I and II.